(untitled) (New Jersey, 2003)
This volume contains the invited talks and contributed papers presented at the workshop on "Testing QCD Through Spin Observables in Nuclear Targets", held at the University of Virginia in April 2002. The workshop was proposed in the context of the large number of experiments that have used polarized deuterons or polarized 3He to extract information about the spin parameters of the neutron. The motivation for this workshop was to study the effects of the nuclear medium on the spin properties of the bound nucleon and to explore issues in QCD that might be resolved through spin observables in nuclear targets: What is the effect of the nuclear medium on the measured asymmetries? How have the latest results on the spin structure of the nucleon and the nucleon form factors changed our thinking? What advances are anticipated in the development of polarized targets?
Keywords: Targets (Nuclear physics),Nuclear reactions,Vật lý hạt nhân,Phản ứng hạt nhân; Congresses,Tài liệu hội nghị, hội thảo